Knowledge management and gamification in Pharma: an approach in pandemic times to develop product quality reviews - Sousa, M. (2021)
The Pharma sector is a much‑regulated market, and this means that this industry must test their products to comply with existing standards to assure the required level of quality and safety before being authorized to lunch those products to the market. Supply chains, data integrity, and tightening regulations are just examples of business process issues that affect quality strategies on a day‑to‑day basis. Besides, regulatory bodies are increasingly focused not only on compliance but also on building a culture of quality management. In this domain, the Quality Management System (QMS)is a well‑known system to support processes, procedures, and responsibilities for achieving quality policies and objectives.The QMS also drives consistent metrics, risk calculations, and other trend analysis in developing periodical Product Quality Reviews (PQRs), usually corresponding to one year periods, related to the product and with its active substance. The PQRs development process requires proper management of knowledge so that it can be replicated in different activities. This paper proposes the adoption of Gamification techniques in each phase of PQRs. In pandemic times, it is importante to improve the performance of each activity, gathering the engagement of the employees. Gamification is usually related to employee motivation, which, in turn, is conducive to the achievement of better results in the organization. In this context, it is necessary to understand how the commitment of stakeholders evolves and if the application of Gamification techniques allows enhancing this variable, taking the evolution of the performance as another variable that could be evaluated. This paper focuses on innovation in the area of knowledge management, based on the projection of a Gamified model related to managing activities of a PQR development project at the level of the active substance. The paper presents a case study where the proposed model was applied to analyze the performance achieves in a national pharmaceutical industry in Portugal.